2015
DOI: 10.1039/c4ob02608j
|View full text |Cite
|
Sign up to set email alerts
|

A new multicomponent reaction: unexpected formation of derivatizable cyclic α-alkoxy isothioureas

Abstract: An unexpected formation of cyclic α-alkoxy isothioureas has been achieved. As is known, the heterocyclic imines 2,5-dihydro-1,3-thiazoles are convertible to bisamides with the aid of a carboxylic acid and an isocyanide (Ugi reaction). Herein, it is shown that 2,5-dihydro-1,3-thiazole S-monoxides-the respective α-sulfinyl imines-are characterized by an altered reaction behavior. In a hitherto unknown multicomponent reaction the α-sulfinyl imines react with an isocyanide under acidic conditions in an alcoholic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Accordingly, they proposed a mechanism that is shown in Scheme . The sulfoxide 127 is protonated by the carboxylic acid and the nucleophilic attack of the alcohol 131 causes a ring-opening to form the sulfenic acid 132 .…”
Section: Cyclic Imines In Joulliè−ugi Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, they proposed a mechanism that is shown in Scheme . The sulfoxide 127 is protonated by the carboxylic acid and the nucleophilic attack of the alcohol 131 causes a ring-opening to form the sulfenic acid 132 .…”
Section: Cyclic Imines In Joulliè−ugi Reactionmentioning
confidence: 99%
“…In 2012, Martens et al discovered an unexpected formation of cyclic α-alkoxy isothioureas 128 (Scheme 40). 132 They wanted to investigate the effect of the sulfoxide moiety on the reactivity of the cyclic imine in JU-3CR. They prepared 3thiazoline S-monoxides 127 as cyclic imines by A-4CR followed by oxidation with the aid of mCPBA.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maes et al reported a three-component reaction using isocyanides, aryl amines, and thiosulfonates under Cu­(I) catalysis, which was thought to proceed through an iminomethylene sulfonium intermediate . Martens et al reported that when certain 2,2- and 5,5,-tetraalkylated 2,5-dihydro-1,3-thiazole S-monoxides were treated with isocyanides in alcoholic solvents in the presence of benzoic acid, isothiourea derivatives were generated, and the reaction was supposed to proceed through a sulfenic acid related reaction pathway . These reports are supportive of our hypothesis that the reaction between benzyl isocyanide and phenyl tert -butyl sulfoxide may also go through sulfenic acid and form an iminomethylene sulfornium intermediate (Scheme ).…”
mentioning
confidence: 99%
“…Recently, Sun et al developed a methodology for the synthesis of isothiourea from sulfoxide, isocyanide, and amine (Scheme e) . Another method was developed by Martens to produce cyclic α-alkoxyisothioureas by treating 3-thiazoline S -monoxides with isocyanides and alcohols under acidic conditions . It has also been reported that the addition of aryl diazoniumfluoroborates to aryl isothiocyanate made from aryl isothiocyanates and secondary amines in the presence of a base such as Et 3 N leads to the formation of N,N -dialkyl- N′ -arylcarbamimido­thioate …”
Section: Introductionmentioning
confidence: 99%